Zepto cataract surgery: The way forward - Nishanth Madhivanan (TNOA Journal of Ophthalmic Science and Research, 2018)
Continuous curvilinear capsulotomy (CCC) is one of the most crucial steps of cataract surgery because of numerous surgical and anatomic advantages. The introduction of cataract surgery assisted by femtosecond laser has improved the repeatability and the accuracy of a perfectly rounded capsulotomy, as compared to the manual CCC. However, multiple surgical steps and the relatively high cost-per case have rendered this technology useful only to the affordable. This article describes a cost-effective and convenient new technique of perfecting the circular capsulotomy using a device called precision pulse capsulotomy or Zepto.